155k views
2 votes
2 ^ x = 3 ^ (x + 1) solve for x

1 Answer

7 votes

Answer:

-2.71

Explanation:

This exponential equation can be solved by rewriting it so there is only one base, then using logarithms.

__

solve for x

2^x = 3^(x+1) . . . . . given

2^x = 3·3^x . . . . . . eliminate the constant in the exponent

(2/3)^x = 3 . . . . . . . divide by 3^x

x·log(2/3) = log(3) . . . . take logarithms

x = log(3)/log(2/3) ≈ -2.7095113

The value of x is about -2.71.

__

Alternate solution

Taking logarithms transforms this exponential equation to a linear equation.

x·log(2) = (x +1)·log(3) . . . . take logs

x(log(2) -log(3)) = log(3) . . . . . . subtract x·log(3)

x = log(3)/(log(2) -log(3)) = log(3)/log(2/3) . . . . . same result as above

_____

Additional comment

In the attached, we have used a graphing calculator to find the x-intercept of the function f(x) = 0, where f(x) = 2^x -3^(x+1). This is the solution to the given equation.

The applicable rules of logarithms are ...

log(a^b) = b·log(a)

log(a/b) = log(a) -log(b)

2 ^ x = 3 ^ (x + 1) solve for x-example-1
User Mradul Pandey
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.